2020
DOI: 10.1038/s41598-020-67613-2
|View full text |Cite
|
Sign up to set email alerts
|

Approximating the maximum tibial coverage in total knee arthroplasty does not necessarily result in implant malrotation

Abstract: Traditionally, the practice of the tibial component placement in total knee arthroplasty has focused on achieving maximum coverage without malrotation. However, the concept of maximizing coverage has not been well defined or researched and yet biased results are often produced. This study aimed to evaluate the effect of a prioritizing maximum coverage positioning strategy on the rotational alignment by using a strict computer algorithm. Computed tomographic scans of 103 tibial specimens were used to reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…It resulted in significantly less malrotated internal components, as it was easier to estimate the relation between tibial rotation and coverage. Results of this study are not confirmed by another study by Shao et al [ 29 ] in which the authors stated that maximizing tibial plateau coverage does not necessarily result in implant malrotation. In our study, choice of technique had a significant impact on the value of tibial baseplate rotation.…”
Section: Discussioncontrasting
confidence: 99%
“…It resulted in significantly less malrotated internal components, as it was easier to estimate the relation between tibial rotation and coverage. Results of this study are not confirmed by another study by Shao et al [ 29 ] in which the authors stated that maximizing tibial plateau coverage does not necessarily result in implant malrotation. In our study, choice of technique had a significant impact on the value of tibial baseplate rotation.…”
Section: Discussioncontrasting
confidence: 99%
“…The design of the base femur component was subtly adjusted for each model to reflect differences in transepicondylar (ML) width between the designs and ensure consistency with the dimensioning used in each of the surgical manuals. The design of the base tibia plate was kept constant and only the 2D profile was used like in prior studies ( Shao et al, 2020 ; Clary et al, 2014 ). A 2D analysis was sufficient for the tibia plate because the components only interface with the resected bone on a singular 2D face.…”
Section: Methodsmentioning
confidence: 99%
“…Poor implant size selection can result in increased rates of complications, revisions, and patient pain post-surgery ( Culler et al, 2017 ; Schroeder and Martin, 2019 ; Buller et al, 2018 ). The presence of regions of OUH ≥3 mm in particular is highlighted as being clinically significant and directly linked with cases of increased soft-tissue irritation, bleeding, osteolysis, laxity in flexion, subsidence, and instability ( Schroeder and Martin, 2019 ; Dai et al, 2014 ; Shao et al, 2020 ). Despite the importance of achieving a good fit, the accuracy of manual X-ray assessment and templating, for both femur components and tibia plates, can be poor.…”
Section: Introductionmentioning
confidence: 99%